Tissue inhibitor of metalloproteinase-3 (TIMP3) expression decreases during melanoma progression and inhibits melanoma cell migration. (October 2016) - Das, Asha M.; Bolkestein, Michiel; van der Klok, Thom; Oude Ophuis, Charlotte M.C.; Vermeulen, Cindy E.; Rens, Joost A.P.; Dinjens, Winand N.M.; Atmodimedjo, Peggy N.; Verhoef, Cornelis; Koljenović, Senada; Smits, Ron; ten Hagen, Timo L.M.; et al.
Abstract: Aims: Malignant melanoma is the most aggressive form of skin cancer, and metastatic dissemination to regional and visceral sites is responsible for the majority of melanoma-related mortalities. In a recent study by our group, we observed reduced expression of tissue inhibitor of metalloproteinase-3 (TIMP3) in the majority of stage III melanoma samples studied. TIMP3 has been reported as a tumour suppressor in several human malignancies, with reduced expression correlating with poor clinical outcome. In this study, we investigated the changes in TIMP3 expression during melanoma progression. Patients and methods: TIMP3 expression was analysed by immunohistochemistry in sequential archived tumour material from stage I/II, stage III and stage IV samples from melanoma patients (n = 33). Protein expression was investigated for associations with disease-free survival and overall survival. Methylation status of the gene promoter was determined using methylation-specific PCR. In vitro assays were used to investigate the functional consequences of TIMP3 expression on behavioural aspects of melanoma cells. Results: We show that TIMP3 expression decreases with melanoma progression although no significant clinical associations were obtained. Analysis of the status of promoter methylation using methylation-specific PCR revealed it to be a low-frequency event in melanoma. Additionally, through gene modulation experiments in melanoma cell lines, we show that TIMP3 negatively regulates cell migration, invasion and anoikis resistance. Conclusions: Collectively, our data suggests that TIMP3 functions as a tumour suppressor in melanoma and negatively regulates several aspects of the metastatic cascade. Highlights: Tissue inhibitor of metalloproteinase-3 (TIMP3) expression in sequential melanoma samples was evaluated by immunohistochemistry. TIMP3 expression decreased with melanoma progression. TIMP3 negatively regulates melanoma cell migration and invasion.